Products of Islamic banking / Nasariatul Azlina Mohd Nasaruddin - Mohd Nasaruddin, Nasariatul Azlina (1997)
This study focus on the Islamic services offered by Bank Islam Malaysia Berhad where it is taken as a model to determine the services of Islamic banking. This project paper includes a description of theory of riba and interest, principles and services of Islamic banking. The main objective of this study is to give a real picture on the services and performance of BIMB.